2008
DOI: 10.1007/s10350-008-9361-x
|View full text |Cite
|
Sign up to set email alerts
|

Abdominoperineal Resection for Anal Cancer

Abstract: Abdominoperineal resection for nonmetastatic anal cancer is associated with a high morbidity rate but may result in long-term survival regardless of the indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
2
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 29 publications
5
52
2
9
Order By: Relevance
“…Several investigations with small patient populations have tried to determine if the indication for APR (persistent vs recurrent disease) is a predictor of survival. Some studies have shown that patients with persistent disease have worse prognosis than those with recurrent disease, while others have reported no difference in survival . This difference in survival can lead to patients with persistent disease being offered additional chemoradiation instead of upfront surgery, even in cases when a curative resection could be offered.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations with small patient populations have tried to determine if the indication for APR (persistent vs recurrent disease) is a predictor of survival. Some studies have shown that patients with persistent disease have worse prognosis than those with recurrent disease, while others have reported no difference in survival . This difference in survival can lead to patients with persistent disease being offered additional chemoradiation instead of upfront surgery, even in cases when a curative resection could be offered.…”
Section: Introductionmentioning
confidence: 99%
“…Malgré les progrès du traitement médical, l'amputation abdominopérinéale (AAP) reste nécessaire chez plus de 27 % des patients atteints d'un carcinome épidermoïde de l'anus [2]. Les indications de la chirurgie sont bien codifiées : persistance de la lésion tumorale malgré la radiochimiothé-rapie, récidive de la lésion ou contre-indication à la radiothérapie.…”
Section: Introductionunclassified
“…Une différence de survie entre récidive locale et poursuite évolutive a été longtemps discutée. Toutefois les dernières études publiées avec plus 50 cas n'ont pas montré de différence pronostique entre ces deux groupes de patients [5,6].…”
unclassified
“…En cas de récidive d'un cancer du canal anal, l'AAP de rattrapage est donc justifiée. Une seconde série importante a été publiée par l'équipe de l'Institut Curie en 2009 avec 83 dossiers revus [6]. Cette série a publiée des résultats extrêmement cohérents et comparables à la série de l'Institut Gustave Roussy avec aucune différence de survie selon le délai de survenue de la récidive et la mise en évidence de l'exérèse R0 comme étant un facteur majeur de survie à cinq ans.…”
unclassified
See 1 more Smart Citation